PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) TERHADAP PENYUSUNAN LAPORAN KEUANGAN PADA KOPERASI PEGAWAI REPUBLIK INDONESIA MOTEKAR - Fanni Tri Pratiwi (Jurnal Akuntansi UMMI, 2021)
This study aims to determine how the application of Financial Accounting Standards Entities Without Public Accountability to the preparation of financial statements in KPRI Motekar. This is done because of the presence of SAK ETAP is expected to be able to help KPRI Motekar to prepare financial statements better. The research methodology used is the method deskriptif with a qualitative approach. The data used is primary and secondary data. The primary data obtained from interviews, observation and documentation. Secondary data were obtained from literature review conducted through theoretical data search that has to do with the object of research that utilizes the data cooperative form of financial statements, books proponents of the theory, and the results of previous studies. The results showed that KPRI Motekar SAK ETAP not apply in its financial statements, because of lack of socialization to the cooperative and the lack of human resources who understand accounting.